Efficient generation of planar diodes n+−n−n+ with tunnel boundaries - Prokhorov, E.D.; Botsula, O.V.; Reutina, O.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
Diodes n+−n−n+ with tunnel or resonant-tunneling lateral boundaries are considered. One side of the boundary of such a diode is a semiinsulating substrate of GaAs, which is grown on the n-layer. Tunneling or resonant-tunneling boundary of finite extent can be located on the opposite side of the boundary. The current-voltage curve and the power characteristics of such diodes are investigated in the mm wide frequency range. It is shown that diodes n+−n−n+ with tunnel or resonant tunneling lateral boundaries have a negative differential conductance over a wide frequency band and can be used for the generation and the amplification. The effects of the location and the extent of the lateral boundaries on the energy and frequency characteristics of a diode are studied.